Generalization of Tichonov and Hausdorff ‎Separation Axiomes in Intuitionistic Fuzzy ‎Special Topological Spaces (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Our goal in this paper is to give definitions of generalized of Tichonov and Hausdorff separation axioms in intuitionistic fuzzy special topological spaces, and study relationships between these spaces with the intuitionistic special topological spaces (X, τ0,1) and (X, τ 0,2) on one hand and intuitionistic fuzzy special topological spaces (X, τ1) and (X, τ2) on the other hand